2021
DOI: 10.1039/d1nr01371h
|View full text |Cite
|
Sign up to set email alerts
|

Review of emerging nanotechnology in bone regeneration: progress, challenges, and perspectives

Abstract: The application of nanotechnology to regenerative medicine has increased over recent decades. The development of materials that can influence biology at the nanoscale has gained interest as our understanding of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 112 publications
0
20
0
Order By: Relevance
“…The success of tissue engineering heavily depends on the performance of the materials. For the desired bone regeneration materials, excellent biocompatibility, controlled biodegradability, appropriate mechanical strength, and suitable porosity to support cell differentiation, growth, and proliferation all should be emphasized (Kim et al, 2013;Freeman et al, 2021;Hajiali et al, 2021). Research on graphene-based nanomaterials has boomed in biomaterial applications over the past few years.…”
Section: Introductionmentioning
confidence: 99%
“…The success of tissue engineering heavily depends on the performance of the materials. For the desired bone regeneration materials, excellent biocompatibility, controlled biodegradability, appropriate mechanical strength, and suitable porosity to support cell differentiation, growth, and proliferation all should be emphasized (Kim et al, 2013;Freeman et al, 2021;Hajiali et al, 2021). Research on graphene-based nanomaterials has boomed in biomaterial applications over the past few years.…”
Section: Introductionmentioning
confidence: 99%
“…Fracture healing is a complex regeneration process. In the past, a large number of studies applied MSCs to treat fracture healing, and nanomaterials have been widely used in the field of tissue regeneration (including bone regeneration) (30,31). In this study, we applied ADMSCs combined with PtNPs in a rat tibial fracture model.…”
Section: Discussionmentioning
confidence: 99%
“…Xing and others have also found that the (3-hydroxybutyrate-3-hydroxyvalerate) nanofibers containing metallic silver particles can promote the differentiation of osteoblasts, at the same time, it has good antibacterial effect and good cell compatibility, can play a certain auxiliary role in the regeneration of osteoblasts [80]. The latest study shows the application of glass-based nanocomposites can used for drug delivery to stimulate bone repair [81]. There are also studies have found that silica nanoparticles inhibit osteoclasts and promote osteoblasts by antagonizing NF-kB, can promote the increasing of bone minerals, as a result, in the prevention of diabetes osteoporosis and bone tissue regeneration can play a positive role , the toxicity of these nanoparticles to the retina at different diameters is under further investigation [82].…”
Section: Othersmentioning
confidence: 97%